Graduação tecnológica no Brasil: crítica à expansão de vagas no ensino superior não universitário - Santos, José Deribaldo Gomes dos (2009)
This theoretical, bibliographic and documental research, based on Marxian onto methodology, is proposed to study, in a general way, the implementation of the Non University Graduate Schools (ESNU), which is named technological degree in Brazil. This kind of course means that the Brazilian Government fragments higher learning into University and Non-University to update neoliberal’s engrainedness. In order to reach that goal, this research specifically analyzes this Non University kind of courses expansion in Brazil; it inspects the evolution in offers, admissions, courses and institutions of this kind in Brazil; it studies which are the proposed pedagogical approaches that support this system; it also pursues an understanding about the strategic role of having a subsystem of higher learning (ES) in our country, facing the present scenery of contemporary capitalism crisis; it additionally verifies the bestowed importance of technological degree in face of the Brazilian necessity to extend people’s access to higher learning. This investigation tried to cover, in a summarized way, the history of some classical theories about education and, respecting its limits, point to some particularities related to professional formation, which, to guarantee privileges to the ones already privileged, distinguishes two alternative education paths: one named professional, to working classes, and other named academic, to the elite. Afterwards, this exposition brings to attention some theoretical questions about the context that surrounds the structural crisis of capitalism (MÉSZÁROS, 2000, 2003, 2005) and the soundness of Gramsci’s Unique School (1968, 2004). It follows showing the history of Brazilian government policies related to professional formation, since military government until nowadays, focusing on two established decrees: numbers 2208/97 and 5154/04; it debates the technology concept, supported by Vieira Pinto’s theory (2008a, 2008b); examines the relation of Government counter reforms and Brazilian universities; discusses in a critical way, supported by Florestan Fernandes (1973, 1975a, 1975b), the Brazilian industrial development theses. In order to rigorously surround the object, the communication visits part of the bibliography that is related to the Pedagogy of the competences; in this way, it understands that this educational paradigm is the base of this higher learning subsystem; after that, it studies the numbers involving ESNU expansion, comparing with international agencies interference, more specifically International Monetary Fund and The World Bank. In its final remarks, this research concludes that the Brazilian Government operates modern artifacts to deeper neoliberal state. The Brazilian technological degree would address the historical necessity of broader access to ES, but, widening the doors to the “house of knowledge“ by the non university way, in a government way and through the Education for All Program (ProUni), privileging entrepreneurs, government, in fact, hinders basic research development, which, in the end, makes more difficult the very development of the country. This investigation closes its arguments strongly registering that the outstanding growth of ESNU numbers should not be used as an indication of its effectiveness, because in a society with 10% of youngsters from 18 to 24 years attending to ES, the technological degree will surely seduce those historically hindered from using universities: the sons of the working class.